Pengaruh Workplace Ostracism Terhadap Voluntary Turnover Intention Pada Karyawan Generasi Milenial di Indonesia - Nadhira, Azkiya; Sianturi, Mia Pratiwi (Innovative: Journal Of Social Science Research, 2025)
The role of the millennial generation in the world of work is increasingly growing and has become dominant, and it turns out that this generation likes to move or leave their workplace, which is also known as voluntary employee turnover. Based on several factors, it can be seen that workplace ostracism is one factor that can encourage voluntary turnover intention in employees. The research method that will be used for this study is a quantitative correlational research method. Correlational research aims to investigate the extent to which a phenomenon in a variable is related to one or more other variables. The results of the study indicate that workplace ostracism has a positive effect on voluntary turnover intention by 80.6%, while the remaining 19.4% is influenced by other factors not examined in this study. The majority of subjects did not experience workplace ostracism behavior, as many as 236 (66.1%). Meanwhile, for voluntary turnover intention, it can be seen that the majority of subjects did not have the desire to turn over in the near future, as many as 171 (47.9%). The purpose of this study is to develop variables that have been studied by previous researchers and build a new concept from the results of this study. This study is expected to serve as a reference for future researchers who wish to examine similar variables and can also serve as a guide for companies to prevent rising turnover rates and ostracism. Future research with similar variables is recommended to examine more specific job fields and conduct more comprehensive data collection.